The Long-Term Effects of Measles Vaccination on Earnings and Employment. A Replication Study of Atwood (American Economic Journal: Economic Policy, 2022) - Mara Barschkett; Mathias Huebener; Andreas Leibing; Jan Marcus; Shushanik Margaryan (Journal of Comments and Replications in Economics (JCRE), 2023)
Atwood analyzes the effects of the 1963 U.S. measles vaccination on long-run labor market out-comes, using a generalized difference-in-differences approach. We reproduce the results of thispaper and perform a battery of robustness checks. Overall, we confirm that the measles vaccinationhad positive labor market effects. While the negative effect on the likelihood of living in povertyand the positive effect on the probability of being employed are very robust across the differentspecifications, the headline estimate-the effect on earnings-is more sensitive to the exclusion ofcertain regions and survey years.
https://doi.org/10.15456/j1.2023335.1653953858
Keywords: I18; I12; J22; J24; J31; 330; Measles Vaccine; Health; Labor Market Outcomes; Robustness; Replication